Modeling and Managing of Random and Sudden Demand of Inventory - Al-Tarawneh, Afrah , M.; Al-Juboori, Salloom , A. (European Scientific Journal, ESJ, 2016)
Inventory management represents an important thing for any company because it is considered as a competitive feature of the company in the market. Owning a high stocks or stock less than the limit required, represents a challenge for the companies, enterprises, and especially in light of exigent circumstances may meet. It is increasingly important when the demand becomes sudden and outside the ordinary situations. This study aims to model and manage the inventory when the demand of product is sudden (unexpected) and how the company can deal with it especially, if there is a limit time for delivery which affects the company work and required additional cost for overtime work. So, a general visual basic computer program was designed and tested to control and manage the inventory in all conditions (i.e. normal and emergency).The program was verified on a case study which is the Jordan Chalk Manufacturing Company. The results of application of the program on the case study have shown that the program can deal with all cases of inventory successfully.